2017
DOI: 10.1038/s41598-017-07091-1
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Lactobacillus salivarius LI01 or Pediococcus pentosaceus LI05 prevents CCl4-induced liver cirrhosis by protecting the intestinal barrier in rats

Abstract: Alterations in the gut microbiome have been reported in liver cirrhosis, and probiotic interventions are considered a potential treatment strategy. This study aimed to evaluate the effects and mechanisms of Lactobacillus salivarius LI01, Pediococcus pentosaceus LI05, Lactobacillus rhamnosus GG, Clostridium butyricum MIYAIRI and Bacillus licheniformis Zhengchangsheng on CCl4-induced cirrhotic rats. Only administration of LI01 or LI05 prevented liver fibrosis and down-regulated the hepatic expression of profibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 45 publications
1
66
1
1
Order By: Relevance
“…Especially, LPS derived from E. coli in portal blood reaches the liver and enhances tissue necrosis factor α (TNFα) production from Kupffer cells through TLR4 signaling and leads to pathological progression of NASH. On the other hand, it is suggested that non-invasive bacteria such as Lactobacillus salivarius, acidophilus and Pediococcus pentosaceus do not induce liver fibrosis, or rather prevent liber fibrosis 6,10,[29][30][31][32] . Lactobacillus acidophilus has anti-inflammatory and antifibrotic activities through inhibiting NF-kB and down-regulating expression of TGF-β1, α-SMA and collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, LPS derived from E. coli in portal blood reaches the liver and enhances tissue necrosis factor α (TNFα) production from Kupffer cells through TLR4 signaling and leads to pathological progression of NASH. On the other hand, it is suggested that non-invasive bacteria such as Lactobacillus salivarius, acidophilus and Pediococcus pentosaceus do not induce liver fibrosis, or rather prevent liber fibrosis 6,10,[29][30][31][32] . Lactobacillus acidophilus has anti-inflammatory and antifibrotic activities through inhibiting NF-kB and down-regulating expression of TGF-β1, α-SMA and collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes, which are relevant to host immunity and metabolism, are key factors contributing to IBD pathogenesis and development (Tamboli et al , 2004; Sartor, 2008; Marion‐Letellier et al , 2016). According to multiple studies, P. pentosaceus LI05 exerts an important effect on protecting the host intestine by regulating the gut microbiome, thereby strengthening the gut barrier and modulating the mucosal immunity, as well as host metabolism (Bengmark et al , 2011; Zhao et al , 2012; Lv et al , 2014b; Shi et al , 2017; Xu et al , 2018). Therefore, our study aimed to evaluate alterations in the gut microbiota, immune responses and metabolites (SCFA production) in a mouse model of DSS‐induced colitis after treatment with P. pentosaceus LI05.…”
Section: Discussionmentioning
confidence: 99%
“…Pediococcus pentosaceus, a member of the family Lactobacillaceae , is a species that has been shown to ameliorate inflammation (Lv et al , 2014a). In addition, several species of P. pentosaceus have been reported to alleviate encephalopathy, acute liver failure, obesity and fatty liver (Bengmark et al , 2011; Zhao et al , 2012; Shi et al , 2017). Our newly isolated probiotic P. pentosaceus LI05 has been shown to protect the host mucosa by strengthening the epithelial barrier function and regulating the host immunity and gut microbiota in mouse models of Clostridium difficile infection and CCl4‐induced cirrhosis (Shi et al , 2017; Xu et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al. () demonstrated that adding 3 × 10 9 cfu/ml of L. salivarius LI01 or Pediococcus pentosaceus LI05 raised the Oscillospira population in the ceca of rats with liver cirrhosis. First identified in pig cecal contents, Oscillospira is a genus that probably produces butyrate and is negatively associated with inflammatory immune responses (Konikoff & Gophna, ).…”
Section: Discussionmentioning
confidence: 99%